2020
DOI: 10.1104/pp.19.01505
|View full text |Cite
|
Sign up to set email alerts
|

Durotropic Growth of Pollen Tubes

Abstract: Pollen tube growth in the style is guided by an active mechanoresponsive system that is sensitive to the stiffness and resistance of the growth path.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…The PTs of the plants with hollow TTs (hPTs), however, showed opposite behavior. Interestingly, the force exerted by the elongating sPTs was recorded far lower (<11 µN for tobacco PT) than that of their hPT counterparts (<36 µN for lily PT) (Reimann et al, 2020). However, the elongation of both types of PTs was halted at excessively high matrix stiffness level (12% agarose).…”
Section: Durotaxis: Pollen Tube Steals a Cellular Movementioning
confidence: 96%
See 2 more Smart Citations
“…The PTs of the plants with hollow TTs (hPTs), however, showed opposite behavior. Interestingly, the force exerted by the elongating sPTs was recorded far lower (<11 µN for tobacco PT) than that of their hPT counterparts (<36 µN for lily PT) (Reimann et al, 2020). However, the elongation of both types of PTs was halted at excessively high matrix stiffness level (12% agarose).…”
Section: Durotaxis: Pollen Tube Steals a Cellular Movementioning
confidence: 96%
“…A recent PT-elongation study by Reimann et al (2020) showed that the PTs of the plants with solid or semi-solid TTs (sPTs) show increased elongation rates in stiffer matrices. The PTs of the plants with hollow TTs (hPTs), however, showed opposite behavior.…”
Section: Durotaxis: Pollen Tube Steals a Cellular Movementioning
confidence: 99%
See 1 more Smart Citation
“…Only when the PT reaches the female gametophyte inside the ovule does it bursts to release the two sperm cells. This journey implicates complex mechanisms that assure PT integrity and growth, adhesion to transmitting tract cells, and molecular communication between the PT and the maternal and gametophytic tissues of the ovule (Lord, 2003;Johnson et al, 2019;Reimann et al, 2020).…”
Section: The Pollen Tube Journey: Interaction With the Transmitting Tmentioning
confidence: 99%
“…During this journey through the female tissues, the CW plays an important role, providing mechanical support and also plasticity enough to permit not only growth but also a dynamic response to the plethora of chemical stimuli to which PTs respond. In this sense, the recently coined term "durotropic growth" refers to a mechano-sensitive growth behavior that contributes to PT guidance in plants with solid or semi-solid transmitting tracts (Reimann et al, 2020). Microtubules are also proposed to stabilize PT under tension, facilitating its growth (Hamant et al, 2019).…”
Section: The Pollen Tube Journey: Interaction With the Transmitting Tmentioning
confidence: 99%